Mechanisms of Modulation of Calcium Phosphate Pathological Mineralization by Mobile and Immobile Small-Molecule Inhibitors - Li, M.; Zhang, J.; Wang, L.; Wang, B.; Putnis, Christine (American Chemical Society, 2018)
© 2018 American Chemical Society. Potential pathways for inhibiting crystal growth are via either disrupting local microenvironments surrounding crystal-solution interfaces or physically blocking solute molecule attachment. However, the actual mode of inhibition may be more complicated due to the characteristic time scale for the inhibitor adsorption and relaxation to a well-bound state at crystal surfaces. Here we demonstrate the role of citrate (CA) and hydroxycitrate (HCA) in brushite (DCPD, CaHPO 4 ·2H 2 O) crystallization over a broad range of both inhibitor concentrations and supersaturations by in situ atomic force microscopy (AFM). We observed that both inhibitors exhibit two distinct actions: control of surface crystallization by the decrease of step density at high supersaturations and the decrease of the [1-00] Cc step velocity at high inhibitor concentration and low supersaturation. The switching of the two distinct modes depends on the terrace lifetime, and the slow kinetics along the [1-00] Cc step direction provides specific sites for the newly formed dislocations. Molecular modeling shows the strong HCA-crystal interaction by molecular recognition, explaining the AFM observations for the formation of new steps and surface dissolution along the [101] Cc direction due to the introduction of strong localized strain in the crystal lattice. These direct observations highlight the importance of the inhibitor coverage on mineral surfaces, as well as the solution supersaturation in predicting the inhibition efficacy, and reveal an improved understanding of inhibition of calcium phosphate biomineralization, with clinical implications for the full therapeutic potential of small-molecule inhibitors for kidney stone disease.